Comparison of Four Rate-Correction Algorisms for the Ventricular Repolarization Period in Assessing Net Effects of IKr Blockers in Dogs - Akira Takahara; Atsushi Sugiyama; Yoshioki Satoh; Keitaro Hashimoto (Elsevier, 2006)
The utility of corrected and uncorrected QT interval changes for assessing net repolarization delay by IKr (a rapid component of delayed rectifier K+ currents) blockers was assessed in halothane-anesthetized dogs using the electrocardiogram and monophasic action potential (MAP) recordings with electrical ventricular pacing. Intravenous administration of dl-sotalol (0.2 - 2 mg/kg) prolonged the MAP duration and RR interval, while terfenadine (3 mg/kg) increased the MAP duration but transiently shortened RR interval. The order of correlation coefficient between the MAP duration at a pacing cycle length of 400 ms and MAP duration itself or that with arithmetical correction was uncorrected > Van de Water = Matsunaga > Fridericia > Bazett. These results suggest that Matsunaga's and Van de Water's formulae would better predict the net repolarization delay in the in vivo canine model. Also, the risk of drug candidates that may prolong the QT interval should be judged by change in uncorrected QT interval as well as corrected QT interval. Keywords:: QT interval, QTc, dl-sotalol, terfenadine, monophasic action potential